Cognitive Load Management in Digital Learning Environments: Implications for Student Performance - Lena Rodrig; L. Marlow (PT Mutiara Bustan Ilmu, 2025)
This study examines the cognitive load management strategies employed in digital learning environments and their implications for student performance. As online and technology-mediated learning continues to expand globally, understanding how cognitive load influences students’ processing of digital instructional materials becomes increasingly crucial. Using a qualitative descriptive approach supported by an analysis of contemporary research in cognitive science and digital pedagogy, the study explores how intrinsic, extraneous, and germane cognitive loads interact within various digital platforms. The findings reveal that poorly designed digital interfaces, excessive multimedia elements, and unstructured tasks significantly increase extraneous load, thereby reducing learning efficiency. Conversely, well-designed instructional scaffolds, adaptive technologies, and structured multimedia integration optimize germane cognitive load, leading to improved comprehension and performance. This study highlights the importance of cognitive load-informed design in digital learning ecosystems and calls for collaborative efforts between educators, instructional designers, and technology developers to ensure effective digital learning experiences.